The Inﬂuence of the Korean Wave on the Consumption of the Iconic Korean Spirit, ‘Soju’, by Thai Consumers - Thanabordeekij, Pithoon (Journal of ASEAN PLUS Studies, 2025)
In recent decades, Korean culture has gained global attention due to globalization and rapid technological advancements. This cultural phenomenon, known as the “Hallyu” or “Korean Wave”, has conferred substantial soft power on Korea through its impact on entertainment media, the arts, fashion, language, and cuisine. The main objective of this research is to examine how Economic Value (ECV), Quality Value (QV), Emotional Value (ETV), Epistemic Value (EPV), Familiarity (FM), Subjective Norm (SN), and Perceived Behavioral Control (PBC) inﬂuence Thai consumers, purchase intentions for Soju, a popular Korean alcoholic beverage, by applying the extension of the Theory of Planned Behavior (TPB). Methodologically, this study employed a quantitative approach, conducting a cross-sectional survey of 464 Thai consumers in Chiang Mai. The collected data were analyzed using the Ordinary Least Squares (OLS) regression method. The study reveals that perceived quality, emotional value, familiarity, subjective norms, and perceived behavioral control have a significant impact on Thai consumers’ purchase intentions for Soju. In contrast, economic and epistemic values do not show significant inﬂuence. Based on these findings, businesses should focus on quality assurance, cultural integration strategies, enhancing product familiarity, leveraging social inﬂuence, and improving product accessibility to expand the Soju market in Thailand eﬀectively. Implementing these targeted marketing approaches can strengthen Thai consumers’ connection to Korean culture and enhance Soju’s market presence nationwide.